T4 ERK5 degradation: a turning point from compensated metabolic cardiomyopathy to heart failure. (21st March 2018) - Ruiz-Velasco, A; Liu, W; Wang, X
Abstract : Rationale: The accumulated prevalence of obesity, diabetes, and metabolic syndrome is more than 25% of the world's population. These are all conditions that have been repeatedly related to a higher risk of heart failure, and effective treatment has not been found. It remains essential to continue deciphering the underlying molecular mechanism to discover novel treatment strategies. Methodology: Initial screening was performed on myocardium samples from ob/ob mice, db/db mice, rhesus monkey with spontaneous metabolic syndrome, and mice fed for 25 weeks with high-fat diet (HFD). In subsequent studies, extracellular signal-regulated protein kinase 5 (ERK5) cardiomyocyte-specific knockout mice (ERK5-cko) were evaluated up until 16 weeks of HFD feeding. In vitro experiments were performed on rat ventricular myocytes treatd with saturated fatty acids. Results: The screening of obese and diabetic models showed that ERK5 was selectively lost in the myocardium. ERK5-cko presented cardiac dysfunction after only 16 weeks of HFD. Further studies showed the loss of contractility was accompanied by augmented oxidative stress, increased lipid accumulation, and severe mitochondrial dysfunction. Mechanistic studies revealed ERK5 to act upstream of the mitochondrial regulator peroxisome proliferator-activated receptor γ co-activator-1α (PGC-1α). Moreover, it was observed that ERK5 degradation after saturated fatty acid treatment was mediated by calpain-1, while the inhibition of this degradation could prevent the mitochondrial dysfunction. Conclusion: The calpain-mediated degradation of ERK5 blunts the compensatory response that would usually maintain mitochondrial integrity when facing metabolic stress.